2021
DOI: 10.3389/fneur.2021.656342
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical and Genetic Analysis of Costa Rican Patients With Parkinson's Disease

Abstract: Background: Most research in genomics of Parkinson's disease (PD) has been done in subjects of European ancestry, leading to sampling bias and leaving Latin American populations underrepresented. We sought to clinically characterize PD patients of Costa Rican origin and to sequence familial PD and atypical parkinsonism-associated genes in cases and controls.Methods: We enrolled 118 PD patients with 97 unrelated controls. Collected information included demographics, exposure to risk and protective factors, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
0
2
0
Order By: Relevance
“…For example, we excluded the study from Costa Rica from the meta-analysis to reduce heterogeneity. The study found no GBA1 variants in patients with PD, probably due to low sample size, the method of sequencing (molecular inversion probes), and a geographical enrollment bias (participants from a specific metropolitan area, in the detriment of metropolitan areas and coastal zones of the country) 15 . Full sequencing of GBA1 in Latinos has already discovered the pathogenic p.K198E variant in Colombia, with a prevalence of 6% in patients with PD, increasing the disease risk six-fold 7 , showing that some variants of clinical relevance may only be reported after sequencing the whole gene.…”
mentioning
confidence: 71%
“…For example, we excluded the study from Costa Rica from the meta-analysis to reduce heterogeneity. The study found no GBA1 variants in patients with PD, probably due to low sample size, the method of sequencing (molecular inversion probes), and a geographical enrollment bias (participants from a specific metropolitan area, in the detriment of metropolitan areas and coastal zones of the country) 15 . Full sequencing of GBA1 in Latinos has already discovered the pathogenic p.K198E variant in Colombia, with a prevalence of 6% in patients with PD, increasing the disease risk six-fold 7 , showing that some variants of clinical relevance may only be reported after sequencing the whole gene.…”
mentioning
confidence: 71%
“…Furthermore, according to this study, p.R1441G is rare in Latin America, even in patients of Spanish ancestry, as one case found, had a different haplotype possibly owing to mixed ancestry [30]. No known pathogenic LRRK2 mutations could be identified in a study assessing the Costa Rican PD population (Clinical and Genetic Analysis of Costa Rican PD population) [31].…”
Section: Lrrk2mentioning
confidence: 49%
“…Regarding Latin American populations, no SNCA pathogenic variants were reported in a study assessing the population of Costa Rica [31]. Moreover, in a cohort of 141 cases from families with apparently dominant PD inheritance in Brazil, no SNCA mutations could be identified [49].…”
Section: Sncamentioning
confidence: 94%
“…This review assessed 3014 studies, of which 73 met the inclusion criteria 20,35–106 . The process detailing the step‐by‐step inclusion and exclusion criteria is summarized in the PRISMA flow diagram 107 shown in Figure S2.…”
Section: Resultsmentioning
confidence: 99%